High Temperature Chloride Corrosion Behavior of 904L:AlFeNiMoNb High-Entropy Alloy - Lingyun Bai (Frontiers Media S.A., 2021)
In order to obtain high cost-effective coating materials working in chlorine-containing environment at high temperature, a 904L super austenitic alloy modified by an AlFeNiMoNb alloy (904L:AlFeNiMoNb) was obtained by vacuum arc melting process. The 904L:AlFeNiMoNb high-entropy alloy has a similar phase component with the AlFeNiMoNb alloy, but a more homogenous microstructure than that of the AlFeNiMoNb alloy. High-temperature chloride corrosion tests for 904L, AlFeNiMoNb, and 904L:AlFeNiMoNb high-entropy alloy were carried out under N2–2.6 vol.% CO2–1.3 vol.% O2–2,700 vppm HCl gaseous environment at 700°C and 800°C for 55 h, respectively. Due to the volatilization of FeCl2, weight change curves of the 904L alloy at 700°C and 800°C showed obvious weight loss. Especially at 800°C, the weight loss of the corroded 904L sample was 10 times that of the corroded sample at 700°C. Different from the weight loss situation of the 904L sample, both AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy showed small weight gains under the corrosion temperature of 700°C, while the latter gained half as much weight as the former. When the corrosion temperature was raised to 800°C, the AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy showed flat weight change curves with little weight loss. Weight loss for the AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy were 1.35138 and 0.0118 mg/cm2, respectively. The high temperature chloride corrosion resistance of 904L:AlFeNiMoNb high-entropy alloy is higher than that of 904L and AlFeNiMoNb at both 700°C and 800°C. Meanwhile, on the basis of the morphology and composition results of the corroded samples, combined with thermodynamic calculation, the high-temperature chloride corrosion mechanics of the tested alloys were discussed.